Pengaruh Pengembangan Karir, Pendidikan Dan Pelatihan Kerja (Diklat) Dan Kedisplinan Terhadap Kinerja Pegawai : Studi Kasus Pada Kantor Dinas Perumahan Dan Kawasan Permukiman Kota Semarang - Kholik, Idam Mafa; Violinda, Qristin; Darmaputra, M. Fadjar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2024)
This research aims to determine the influence of Career Development, Education and Training (training) and Discipline on employee performance (case study at the Semarang City Housing and Settlement Area Office). This research uses a non-probability sampling technique using a saturated sample method. Data processing used the SPSS version 25 program. The population used in this research were civil servants at the housing and residential area services in the city of Semarang and the sample used was 150 respondents. The data in this study used Likert scale measurements, the data collection process was carried out using a questionnaire or manual paper for 150 respondents. The results of the analysis and discussion show that there is an influence. The results of this research show that there is a positive and significant influence between the variables Career Development, Education and Training (training) and Discipline on employee performance. The results of testing the coefficient of determination obtained a value of Adjusted R Square Adjusted R Square of 0.383 . So it can be concluded that the variables career development, education and training (training) and discipline influence employee performance by 38.3% while the remaining 61.7% comes from other variables outside the model which were not examined in this research.